A study on different types of moral courage and coping styles of clinical nurses: based on potential profile analysis - Nian Hong; Niu Qichao; Chen Dong; Tai Chunling; Pang Dong; Lv Xinyu; Su Yu; Liu Shilong; Zhang Yuhuan (BMC, 2023)
Abstract Background In professional ethics-related events, there are various unpleasant and complex ethical issues that require strong moral courage. Our aim is to identify and describe the potential categories of moral courage among nurses and to clarify the coping styles of nurses under different categories. Method A cross-sectional study was conducted using three data collection tools: a self-designed general information questionnaire, a Chinese version of the Moral Courage Scale, and a Trait Coping Style Questionnaire. Three hundred fourteen nurses from a tertiary hospital in Heilongjiang Province, China, were analysed using potential profile analysis, descriptive analysis, and Mann-Whitney U test data. Result The latent profile analysis (LPA) results indicate that the two-profile model is the most suitable and supports the existence of two different moral courage profiles: the low moral courage group (60.51%) and the high moral courage group (39.49%), with a high relative entropy value (0.922). The results point to a good profile solution, and there are significant differences between the two profiles. The Mann-Whitney U-test results showed that the positive coping scores of the high moral courage group were significantly higher than those of the low moral courage group, and the negative coping scores of the high moral courage group were significantly lower than those of the low moral courage group. Conclusion Our results reveal the heterogeneity of moral courage in the nurse sample and indicate that nurses in the high moral courage group tend to choose positive coping styles, while nurses in the low moral courage group are more likely to develop negative coping emotions. This provides important significance and reference value for nursing managers, who can propose customised management plans based on the types of moral courage of the nursing community and the coping styles under different categories.